Influence of The Design of The Rolling Roller on The Quality of The Surface Layer During Plastic Deformation on the Workpiece - Qosimova Z.M; RubidinovSh.G (International Journal on Human-Computing Studies, 2021)
The method of surface plastic deformation of the outer diametrical surfaces of machine parts, where the deformation is transferred by the tool element, which is a rolling tool with two working profile radii, and the tool is additionally imparted with a rotational motion about the OX axis passing through the plane connecting the two rollers and perpendicular to the axis OY blanks. The effect of deformation kinematics on the quality characteristics of the hardened layer of manufactured parts is considered: roughness, residual stresses, workhardening depth, hardness HRC, HB and microhardness. The analysis of the efficiency of parts hardening when machining with a roller with two radii, in comparison with deformation by a roller with one radius